The biography of cultures: style, objects and agency - Caroline van Eck; Miguel John Versluys; Pieter ter Keurs (Les Cahiers de l'École du Louvre)
It is evident that artefacts possess agency; but how do they acquire it, and what role does their material and style play in this? Does part of the agency of artefacts consist in their migration from one cultural context to another? If so, what role does a change of cultural context play in the accumulation of the artefact’s agency? And, to phrase this question from the perspective of the object: what role do artefacts play in the constitution and transference of culture? We will consider these questions by means of a comparison between the presence and agency of “things Greek” in the Augustan and Napoleonic eras. In both periods styles from the past were revived. It is traditionally argued that this happens because of the formal, aesthetic or artistic qualities of these objects. We hope to show, however, that in order to understand the underlying agency of these qualities, it is necessary to study the relative meaning these styles had acquired throughout their cultural biography. Both the Augustan and the Napoleonic eras are characterized by an unprecedented availability of artefacts from all over the world and from many historical periods. This forced those involved in the appropriation, emulation or creation of artefacts to adopt a position towards their own cultures and the shock of the new, be it in terms of the archaic, the classical or what came to be defined as the primitive.